Build It Better: Tinkering in Feminist Maker Pedagogy. - Cipolla, Cyd (Women's Studies)
The author describes a framework for feminist maker pedagogy implemented in a technoscience studies course, starting with its roots and related theories and then moving to reflections from her own practice at New York University. She explains the goals of the pedagogy, including learning about everyday objects in a generative, critical sense. She also discusses how her practice in feminist maker pedagogy fosters personal experimentation.